2014
DOI: 10.1111/cns.12285
|View full text |Cite
|
Sign up to set email alerts
|

Role(s) of the 5‐HT2C Receptor in the Development of Maximal Dentate Activation in the Hippocampus of Anesthetized Rats

Abstract: In our animal model of TLE, mCPP and lorcaserin were anticonvulsant; likely acting on receptor subtypes other than 5-HT2C. Epileptogenesis induced early adaptive changes and reorganization in the 5-HT2CR and GABA systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 54 publications
5
41
0
Order By: Relevance
“…Thus, the fact that epilepsy and depression may share common pathogenic mechanisms and dysfunction of the serotonergic system is an obvious explanation for this bidirectional comorbidity, since defects in the serotonergic system are linked to both conditions ( Epps et al, 2012 ; Epps and Weinshenker, 2013 ). In agreement, we have showed further evidence of the involvement of both serotonergic and dopaminergic systems in the pathogenesis of epilepsy ( Cavaccini et al, 2012 ; Orban et al, 2013 ; Yague et al, 2013 ; Connelly et al, 2014 ; Crunelli and Di Giovanni, 2014 ; Orban et al, 2014 ), in depression and its pharmacological treatments ( Di Giovanni, 2008 ; Esposito et al, 2008 ). Compelling evidence for the involvement of 5-HT 1A - and 5-HT 7 -Rs in epilepsy and depression has been described, therefore it is possible to infer that agonists at these receptors might have both antiepileptic and antidepressant activity with also cognitive enhancer efficacy ( Orban et al, 2013 ).…”
Section: Do the 5-ht2a-rs Play A Role In The Comorbidity Between Epilsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the fact that epilepsy and depression may share common pathogenic mechanisms and dysfunction of the serotonergic system is an obvious explanation for this bidirectional comorbidity, since defects in the serotonergic system are linked to both conditions ( Epps et al, 2012 ; Epps and Weinshenker, 2013 ). In agreement, we have showed further evidence of the involvement of both serotonergic and dopaminergic systems in the pathogenesis of epilepsy ( Cavaccini et al, 2012 ; Orban et al, 2013 ; Yague et al, 2013 ; Connelly et al, 2014 ; Crunelli and Di Giovanni, 2014 ; Orban et al, 2014 ), in depression and its pharmacological treatments ( Di Giovanni, 2008 ; Esposito et al, 2008 ). Compelling evidence for the involvement of 5-HT 1A - and 5-HT 7 -Rs in epilepsy and depression has been described, therefore it is possible to infer that agonists at these receptors might have both antiepileptic and antidepressant activity with also cognitive enhancer efficacy ( Orban et al, 2013 ).…”
Section: Do the 5-ht2a-rs Play A Role In The Comorbidity Between Epilsupporting
confidence: 88%
“…The role of pharmacological activation of 5-HT 2A -Rs in epilepsy modulation is far from being well-established, however, it might be an important potential target in light of the recent evidence that their activation might be not only be anticonvulsant but also capable of reducing seizure-related mortality due to SUDEP ( Buchanan et al, 2014 ), the leading cause of death in patients with refractory epilepsy ( Shorvon and Tomson, 2011 ). In addition, we have recently shown that mCPP and lorcaserin, two preferential 5-HT 2C -R agonists with different pharmacological profiles ( Fletcher and Higgins, 2011 ; Higgins et al, 2013 ), stop the elongation of MDA and AD induced by repetitive perforant path stimulation recorded at the level of the granular cells of the hippocampal DG acting in urethane-anesthetized rats, an effect that was not blocked by SB242084, a selective 5-HT 2C -R antagonist ( Orban et al, 2014 ). The elongation of the MDA has been considered an electroencephalographic representation of epileptogenic phenomena occurring after the first electric insult ( Stringer et al, 1989 ; Orban et al, 2013 ).…”
Section: The 5-ht 2a -Rs In the Regulation Of Epilmentioning
confidence: 99%
“…Indeed, 5-HT 2C R agonists with different pharmacological profiles such as meta-chlorophenylpiperazine (mCPP) and lorcaserin, but not RO60-0175, were able to stop the elongation of the electrically triggered hippocampal maximal dentate gyrus activation in a limbic seizure model in anesthetized rats, an effect that was not blocked but rather potentiated by pre-treatment of SB 242084 (Orban et al, 2014), a selective 5-HT 2C R antagonist. In addition, 5-HT 3 Rs display also no importance in focal hippocampal seizures (Watanabe et al, 1998).…”
Section: Monoamines In Epilepsy: Preclinical and Clinical Evidencementioning
confidence: 99%
“…MDA was electrophysiologically characterized by (1) the onset of large-amplitude ( i.e ., 20–40 mV) population spikes (PSs) fired in bursts, and (2) a rapid increase in amplitude of DG PS 28 29 . Stimulus trains of 10 s (pulses of 0.3 ms duration, at 20 Hz) were delivered through the PP electrode at an initial intensity of 200 μA.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the information available about the various roles of Hsp60 in the central nervous system, in the present study we firstly investigated the expression and distribution of Hsp60 in the rat hippocampus. We used a model of partial complex (limbic) seizures, based on the phenomenon of maximal dentate activation (MDA) recorded in the dentate gyrus (DG), which is induced by repetitive electrical stimulation of the perforant path (PP) in anesthetized rats 27 28 29 . The analysis was conducted using Western blotting and immunohistochemistry on hippocampal tissue samples.…”
mentioning
confidence: 99%